Perceived Impact of Quality Assurance on Teachers’ Job Performance in Nigerian Context - Almustapha, Jibril; Dahiru, Abbas Sani; Abubakar, Hafsatu; Ibrahim, Raihana Kabir (International Journal of Educational and Psychological Sciences, 2024)
This study was purposely conducted on the assessment of the impact of quality assurance on teachers’ job performance in senior secondary schools in Gusau Education Zone, Zamfara State, Nigeria. To maintain accuracy of the results, the data analysis was conducted on Statistical Package for the Social Science (SPSS) version ‘29. The study expressed the statistical value of (r=0.613, P<0.05), denoting that there exist a moderate significant relationship between quality assurance and teachers’ job performance among senior secondary schools in Gusau education zone, Zamfara State. Based on findings the study recommends that there is need for the government should encourage quality assurance in education by providing human and financial resources required for effective quality assurance exercise in public secondary schools. The government in collaboration with relevant stakeholders in educational sector should maintain the culture of trainings, workshops, and seminars for teachers and school administrators to participate in the process of actualising an efficient quality assurance practices. Furthermore, school principals and in-service teachers should support the government’s policies in promoting quality assurance initiatives while discharging the professional duties in their respective schools.